Lower Activation in Frontal Cortex and Posterior Cingulate Cortex Observed during Sex Determination Test in Early-Stage Dementia of the Alzheimer Type - Rajmohan, Ravi; Anderson, Ronald C.; Fang, Dan; Meyer, Austin G.; Laengvejkal, Pavis; Julayanont, Parunyou; Hannabas, Greg; Linton, Kitten; Culberson, John; Khan, Hafiz; De Toledo, John; Reddy, P. Hemachandra; et al. (Frontiers in Aging Neuroscience, 2017)
Face-labeling refers to the ability to classify faces into social categories. This plays a critical role in human interaction as it serves to define concepts of socially acceptable interpersonal behavior. In the current study, four (1 female, 3 male) participants with early-stage clinically diagnosed dementia of the Alzheimer type (CDDAT) and nine (4 female, 5 male) age-matched neurotypicals (NT) completed the sex determination test (SDT) using chimeric faces while undergoing BOLD fMRI. It was expected that CDDAT participants would have poor verbal fluency, which would correspond to poor performance on the SDT. This could be explained by decreased activation and connectivity patterns within the fusiform face area (FFA) and anterior cingulate cortex (ACC). DTI was also performed to test the association of pathological deterioration of connectivity in the uncinate fasciculus (UF) and verbally-mediated performance. CDDAT showed lower verbal fluency test (VFT) performance, but VFT was not significantly correlated to SDT and no significant difference was seen between CDDAT and NT for SDT performance as half of the CDDAT performed substantially worse than NT while the other half performed similarly. BOLD fMRI of SDT displayed differences in the left superior frontal gyrus and posterior cingulate cortex (PCC), but not the FFA or ACC. Furthermore, although DTI showed deterioration of the right inferior and superior longitudinal fasciculi, as well as the PCC, it did not demonstrate significant deterioration of UF tracts. Taken together, early-stage CDDAT may represent a common emerging point for the loss of face labeling ability.